Matarenda/Talents in Zimbabwean Pentecostalism : Empowerment, Gender and Development in an African Movement - Chingarande, Sunungurai D.; Anderson, Allan H.; Madziva, Roda; Thondhlana, Juliet (Global Pentecostal and Charismatic Studies, 2021)
In Matarenda/Talents in Zimbabwean Pentecostalism , the fourteen contributors to this multidisciplinary collection reflect on how Pentecostalism contributes to the empowerment of marginalised societies, how it empowers women in particular through the matarenda (talents) principles, and how it contributes to the development of wider society. All but three of the authors are Zimbabwean Pentecostals. The book deals with such subjects as gender equality, economics and finance, poverty alleviation and sustainable development, education, and entrepreneurship. A remarkable independent Zimbabwean church has harnessed biblical principles from the Parable of the Talents to empower women and those marginalised by economic disasters. It is particularly relevant for understanding the potential of African Pentecostalism in dealing with social and economic challenges.